Real option and vertical mixed-use development - Zhong, Jiawei; Hui, Eddie C. M. (International Journal of Strategic Property Management, 2021)
Vertical mixed-use development is a favourite choice in urban development in high-density Asian cities to increase the land use efficiency. The flexibility of construction timing and the restrictions by lease contracts in vertical mixeduse projects are usually different from horizontal ones and single-use properties. To improve the valuation for vertical mixed-use projects, this study re-examines the real option pricing model. Simultaneous development for different uses and a finite maximum waiting period are the major characteristics of these projects. An approach is introduced to determine whether to develop a mixed-use project vertically or horizontally on the basis of a statistics called the critical height premium. The vertical mixed-use project pricing model can be further verified by containing a height premium if market price information is derived from non-vertical mixed-use properties. This study suggests a more comprehensive real option approach to quantify the advantages and disadvantages of operating vertical mixed-use developments.